Protease-antiprotease imbalance in bronchiectasis - Oriano, Martina (2021)
Airway inflammation plays a central role in bronchiectasis. Protease-antiprotease balance is crucial in bronchiectasis pathophysiology and increased presence of unopposed proteases activity may contribute to bronchiectasis onset and progression. Proteases' over-reactivity and antiprotease deficiency may have a role in increasing inflammation in bronchiectasis airways and may lead to extracellular matrix degradation and tissue damage. Imbalances in serine proteases and matrix-metallo proteinases (MMPs) have been associated to bronchiectasis. Active neutrophil elastase has been associated with disease severity and poor long-term outcomes in this disease. Moreover, high levels of MMPs have been associated with radiological and disease severity. Finally, severe deficiency of α1-antitrypsin (AAT), as PiSZ and PiZZ (proteinase inhibitor SZ and ZZ) phenotype, have been associated with bronchiectasis development. Several treatments are under study to reduce protease activity in lungs. Molecules to inhibit neutrophil elastase activity have been developed in both oral or inhaled form, along with compounds inhibiting dipeptydil-peptidase 1, enzyme responsible for the activation of serine proteases. Finally, supplementation with AAT is in use for patients with severe deficiency. The identification of different targets of therapy within the protease-antiprotease balance contributes to a precision medicine approach in bronchiectasis and eventually interrupts and disrupts the vicious vortex which characterizes the disease.